"Karakalpak yurt" - Qanatova Asel Quat qizi (Zien Journals, 2022)
The question of the origin of a nation has always been a topical one in science. Year after year, thanks to conducted researches, this question has been replenished with scientifically grounded facts. In this article we have considered questions about the dwellings and settlements of Karakalpaks.
Keywords: ethnographic; Karakalpak; Khorezm; research